It’s dangerous: glorification of risk in the media and young people’s attitudes towards driving (Intercom - Brazilian Journal of Communication Sciences, 2022)
This article analyzes short-term media effects of car commercials on TV that glorify risk, and longterm associations, such as the use of violent videogames, on the attitudes of young people towards driving experience. The study, a between-subjects experimental design, included 106 undergraduate students from the Universidade de Brasília (University of Brasília, UnB) during the first semester of 2019. The results show that the short-term effects of exposure to car commercials on TV that glorify risk significantly increase risky attitudes in relation to driving, measured by the Driver Thrill Seeking Scale (DTSS). But this only occurs among individuals who like violent videogames such as Grand Theft Auto (GTA). No short-term effects were found among the other participants, which does not exclude the existence of other types of effect, such as long-term ones.
Keywords: Glorification of risk; Car commercials on TV; Video games; Traffic safety; Driver Thrill Seeking Scale